A Study Assessing Surgical Management of Traumatic Orbital Fractures with Delayed Presentation at Tertiary Care Institutions: An Experience of 1 Year - Dixit, Sourabh; Banga, Manpreet Singh; Saha, Suniti Kumar; Roy, Kaushik; Ghosh, Partha; B.V, Sandeep (Indian Journal of Neurotrauma, 2017)
Background Orbital and periorbital injuries are significant contributors to traumatic facial injuries. Orbital fractures can occur either alone or in conjugation with other facial bone fractures and cranial and maxillofacial injuries. Objectives The study aims to find out the incidence of various types of fractures occurring in patients, mode of trauma, clinical presentation, and results of delayed surgical repair in cases of orbital fractures.Materials and Methods This is a “prospective observational study” including 12 patients. Surgical repair of orbital fractures was considered for suspected muscle entrapment in fractures, restricted ocular motility, symptomatic diplopia not improving for over 2-week period, or if enophthalmos greater than 2 mm was present.Results Regarding age incidence, the maximum number of cases, that is 41.66%, were aged between 21and 30 years. The main modes of trauma in most cases, that is, 50%, were due to road traffic accidents followed by fall from height, that is, 25%. The majority of cases presented to us with complex fractures involved one or more orbital bones, that is 33.33%. Postsurgery outcomes were good and fair in 75% and 25% patients, respectively.Conclusion Proper orbital fracture stabilization is crucial to bring out good cosmetic as well as ocular outcome.
Keywords: orbital fractures; diplopia; enophthalmos